Mature dendritic cells boost functionally superior CD8(+) T-cell in humans without foreign helper epitopes - Dhodapkar, Madhav V. (American Society for Clinical Investigation, 2000)
We have recently shown that a single injection of mature, antigen-pulsed, human dendritic cells (DCs) rapidly elicits CD4(+) and CD8(+) T-cell immunity in vivo. The DCs were pulsed with 2 foreign proteins, keyhole limpet hemocyanin (KLH) and tetanus toxoid (TT), as well as an HLA A2.1-restricted influenza matrix peptide (MP). Responses to all 3 antigens peaked at 30–90 days after immunization and declined thereafter. To determine if the foreign helper proteins (TT and KLH) were essential for CD8(+) T-cell responses to the viral peptide, we reinjected 3 of the HLA-2.1 subjects with mature DCs pulsed with MP alone. All 3 volunteers showed a rapid boost in MP-specific immunity, and freshly sampled blood from 1 contained cytolytic T cells. In all 3 subjects, CD8(+) T-cell responses to booster DCs were faster and of greater magnitude than the responses to the first DC injection. Importantly, the T cells that proliferated after booster DC treatment secreted interferon-γ upon challenge with much lower doses of viral peptide than those elicited after the first injection, indicating a higher functional avidity for the ligand. These data begin to outline the kinetics of T-cell immunity in response to DCs and demonstrate that booster injections of mature DCs enhance both qualitative and quantitative aspects of CD8(+) T-cell function in humans. This article may have been published online in advance of the print edition. The date of publication is available from the JCI website, http://www.jci.org. J. Clin. Invest. 105:R9–R14 (2000).